2016
DOI: 10.1177/0022002715595864
|View full text |Cite
|
Sign up to set email alerts
|

Military Size and the Effectiveness of Democracy Assistance

Abstract: Countries interested in the promotion of political development often provide aid in the form of democracy assistance. However, some regimes resist these attempts to promote democracy, introducing repressive measures to counteract their effectiveness. Hence, democracy assistance sometimes has the unintended consequence of curtailing democracy. This article explains how the size of the targeted regime’s military determines the effectiveness of democracy assistance and why it can sometimes result in lower levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 98 publications
(101 reference statements)
0
20
0
Order By: Relevance
“…Building on this conceptualization of backsliding as the erosion of one or more of these democratic institutions by elected officials, this chapter then develops (Berman, 2016;Hanley and Sikk, 2016;Hernandez and Kriesi, 2016;Krastev, 2016;Rupnik, 2016), no systematic theories of this phenomenon exist (Waldner and Lust, 2018). On the international side, authors have critiqued democracy assistance and suggested it can even have deleterious effects (Bush, 2015;Henderson, 2003;Savage, 2017;Wedel, 2001), while others have shown how regional powers may engage in autocracy promotion (Finkel and Brudny, 2012). However, few have investigated the role of IOs in particular and how they might be contributing to these illiberal trends.…”
Section: Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on this conceptualization of backsliding as the erosion of one or more of these democratic institutions by elected officials, this chapter then develops (Berman, 2016;Hanley and Sikk, 2016;Hernandez and Kriesi, 2016;Krastev, 2016;Rupnik, 2016), no systematic theories of this phenomenon exist (Waldner and Lust, 2018). On the international side, authors have critiqued democracy assistance and suggested it can even have deleterious effects (Bush, 2015;Henderson, 2003;Savage, 2017;Wedel, 2001), while others have shown how regional powers may engage in autocracy promotion (Finkel and Brudny, 2012). However, few have investigated the role of IOs in particular and how they might be contributing to these illiberal trends.…”
Section: Next Stepsmentioning
confidence: 99%
“…However, there are a few important exceptions. Several authors have critiqued democracy assistance and suggested it can even have deleterious effects (Bush, 2015;Henderson, 2003;Savage, 2017;Wedel, 2001), while others have shown how regional powers may engage in autocracy promotion (Finkel and Brudny, 2012;Whitehead, 2015). Nevertheless, no studies have explicitly hypothesized or tested the extent to which international actors may unintentionally create conditions that make democratic backsliding more likely at the domestic level.…”
Section: Existing Theories Of Democratic Backslidingmentioning
confidence: 99%
“…For example, the risk of backlash varies depending on the size of the military. Recent research shows that democracy promotion is more likely to trigger repression when recipients have larger armed forces (Savage, ). Democracy supporters therefore need to take account not only the danger of authoritarian backlash, but also the fact that this risk is likely to be higher in those countries in which the coercive capacity of the state is highest – compounding the challenge of difficult cases.…”
Section: Ten Challenges In Democracy Supportmentioning
confidence: 99%
“…16 Technical assistance focuses on improving election management and boosting administrative capacity, which can entail filling equipment gaps (purchasing ballot boxes, ballots, staining ink) and building institutional 13 See Carothers 1997, 112-115;and Burnell 2000, 29-30. 14 See Finkel et al 2007, Savun and Tirone 2011, Scott and Steele 2011, Dietrich and Wright 2015, Bush 2015, and Savage 2015 as the smallest USAID democratic governance category "elections and political processes," which includes observation, technical election assistance, and political party support. 15 See, e.g., Hyde 2011a, Kelley 2012 See Carothers 1999, 125-128;Bjornlund 2004, 60-62.…”
Section: Background On Technical Election Assistancementioning
confidence: 99%